IGARSS 2003. 2003 IEEE International Geoscience and Remote Sensing Symposium. Proceedings (IEEE Cat. No.03CH37477)
DOI: 10.1109/igarss.2003.1294055
|View full text |Cite
|
Sign up to set email alerts
|

Permanent Scatterers: precision assessment and multi-platform analysis

Abstract: The Permanent Scatterers (PS) technique is an advanced tool for processing series of interferometric SAR data aiming at millimetric precision ground deformation mapping. The approach is based on a joint time-space-acquisition geometry analysis that is carried out at individual point-wise radar targets. The aim of this paper is twofold: (1) describe the main issues related to the precision of PS products; (2) show preliminary PS results obtained using, instead of ESA-ERS scenes, data acquired by other spaceborn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
0
13
0
Order By: Relevance
“…The resolution achieved by the identification of these PS targets in long temporal series of SAR images creates a data set consisting of many "radar benchmarks" where target displacement information can be accurately estimated due to favorable reflectivity conditions. The advantages of the PS methodology are: (1) good phase coherence over the sparse PS grid, from nearly all radar scenes, regardless of geometrical baseline (i.e., separation of satellite trajectories involved in the generation of the interferograms); (2) as all interferograms are generated using a single master scene, the mathematical framework allows the user to take advantage of procedures for the assessment of the precision [Colesanti et al, 2003a]; and (3) by exploiting a long time series of radar data, atmospheric phase contributions can be estimated and removed from the deformation phase signal by proper filtering procedures, thus significantly increasing the accuracy of the measurements. PSs correspond to persistent, bright radar reflectors, such as buildings, poles, metallic structures, exposed rocks or other similar objects.…”
Section: Psinsar Methodologymentioning
confidence: 99%
“…The resolution achieved by the identification of these PS targets in long temporal series of SAR images creates a data set consisting of many "radar benchmarks" where target displacement information can be accurately estimated due to favorable reflectivity conditions. The advantages of the PS methodology are: (1) good phase coherence over the sparse PS grid, from nearly all radar scenes, regardless of geometrical baseline (i.e., separation of satellite trajectories involved in the generation of the interferograms); (2) as all interferograms are generated using a single master scene, the mathematical framework allows the user to take advantage of procedures for the assessment of the precision [Colesanti et al, 2003a]; and (3) by exploiting a long time series of radar data, atmospheric phase contributions can be estimated and removed from the deformation phase signal by proper filtering procedures, thus significantly increasing the accuracy of the measurements. PSs correspond to persistent, bright radar reflectors, such as buildings, poles, metallic structures, exposed rocks or other similar objects.…”
Section: Psinsar Methodologymentioning
confidence: 99%
“…Colesanti et al (2003) suggested that in an 223 operational context under very good conditions (large data sets -i.e. >30 images, dense PS 224 network, quasi linear deformation regimes), the precision could reach 0.5 mm/y for the annual 225 deformation rate and 3 mm for the displacement values at given acquisition dates for PSI 226 based on data from ERS, Envisat/ASAR or equivalent (C-band, resolution ~10m, 227 repetitiveness of ~ 1 month).…”
Section: Hanssen 2005) 221mentioning
confidence: 99%
“…Each point of the four PS shapefile datasets is identified by coordinates (North, East) and a set of attributes, including: (a) identifier code; (b) average velocity of entire acquisition time period, expressed in mm year −1 ; (c) standard deviation of the average velocity; (d) coherence; and (e) a subset of measurements (expressed in mm) of the displacement along the LOS of each PS. The PS coherence is a normalized index of the local signal-to-noise ratio of the interferometric phase and reflects the accuracy of PS measurements [14,[74][75][76]. PSI processing allows us to obtain very accurate measurements within 1.0 mm/year for the PS average velocity along the LOS by assuming a threshold value of 0.65 for coherence [33,71,75,77,78] thanks to the large number of SAR images used for the processing (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…The PS coherence is a normalized index of the local signal-to-noise ratio of the interferometric phase and reflects the accuracy of PS measurements [14,[74][75][76]. PSI processing allows us to obtain very accurate measurements within 1.0 mm/year for the PS average velocity along the LOS by assuming a threshold value of 0.65 for coherence [33,71,75,77,78] thanks to the large number of SAR images used for the processing (Table 1).…”
Section: Methodsmentioning
confidence: 99%